August Rush - Sheridan, Kirsten; Highmore, Freddie, 1992-; Russell, Keri, 1976-; Rhys-Meyers, Jonathan, 1977- (Burbank, CA : Warner Home Video, 2008)
Having been orphaned and working as a street musician, a musically talented kid uses his gift to find his birth parents.
Originally released as a motion picture in 2007.
Features: additional scenes.
Freddie Highmore, Keri Russell, Jonathan Rhys-Meyers, Terrence Howard, Robin Williams.
MPAA rating: PG.
DVD, Dolby digital 5.1 surround.
In English, French, or Spanish with optional English, French, or Spanish subtitles.
Keywords: Orphans -- Drama; Child musicians -- Drama; Musical films; Video recordings for the hearing impaired; Fiction films; Feature films